De l’affordance injonctive à la créativité discursive : l’exemple du ticker numérique - Catherine Ruchon (Corela)
In this article, we will question the affordances, in other words the "actancial signs" (Uexküll 1934), the "valences" or the "character of demand" (Werner 1926) of iconotextual digital objects (Nerlich 1990) such as the numerical time scale called ticker. Form of architext (Genette 1979, Jeanneret and Souchier 2005), the ticker proposes an iconic and linguistic model which simultaneously encourages the action while limiting this field of action. The diversity of affordances seems to depend on the intrinsic potentialities of the object but also on the user's experience. As this coefficient of diversity increases, so does the possibility of exceeding the injunctive level of affordance. Despite of the affordances expected by designers and their intentionality, users "divert" the functionalities of digital objects by retaining the original design but changing the textual elements that accompany it, creating a new, more invisible category of produsage (Bruns 2007, 2008).